Ekoteologi dalam Aksi: Membangun Kepedulian terhadap Lingkungan di Jemaat HKBP Hasahatan - Simanjuntak, Joksan; Simatupang, Eriko; Sagala, Evans (Publikasi Indonesia, 2025)
This research discusses the importance of socialising to the public about the environmental impact of factory waste. Industrial waste is often the main cause of water, air and soil pollution, which directly affects human health and ecosystem sustainability. Through proper socialisation, communities around industrial estates can better understand the negative impacts of factory waste as well as ways to reduce and manage waste more wisely. This study aims to evaluate the effectiveness of socialisation programmes related to mill effluent management, including how information on effluent hazards and mitigation measures are conveyed to the community. The methods used in this study include surveys, interviews, as well as observations in the environment around the factory, with a focus on community perceptions before and after socialisation. The results showed that intensive socialisation involving active community participation was able to raise awareness and encourage environmentally friendly behaviour. The findings also show that collaboration between the factory, government and community is needed to create a sustainable solution for waste management. In conclusion, socialisation of factory waste plays an important role in building better environmental awareness in the community and reducing the negative impact of industry on the surrounding environment.